1)2x³-x³+7x2+x-4x²-5х=2x³-x³+14+x-4x²-5x=x³+14-4x-4x²=x³-4x²-4x+14 при х=2
2³-4*2²-4*2+14=8-2⁴-8+14=8-16-8+14=-2
2) 0,46³ -0,26² +0,56 -0,363-0,56+7=≈6.666736
3) -4a²b+3ab2 +3a²b-5ab2+5а²b=4a²b+3ab2-5ab2=4a²b-2ab2=4a²b-4ab=4ab(a-1) при а=5 b=-0.4=4*5*(-0.4)(5-1)=4*5(-0.4)*4=-32
4) -0,3x-13xy2-37ху²=-0,3x-(13*2)xy-37xy²=-0,3x-26xy-37xy² при х=4 у=-0,2 =-0,3*4-26*4*(-0,2)-37*4*(-0,2)²=4(-0,3+26*0,2-37*(-0,2)²)=4(-0,3+5,2-37*0,2²)=4(-0,3+5,2-37*)=4(-0,3+5,2-)=4(-0,3+5,2-1,48)=4*3,42=13,68
Объяснение:
получится
5^6*(5^2+1)=5^6*(26)
2*5^7 в знаменателе =5^6*5*2
так как 5^7=5^6*5
получилось
5^6*26/5^6*5*2
сокращаешь 5^6 и 26 с 2
остаётся
13/5